The John W. Knutson Distinguished Service Award in Dental Public Health-2000 Recipient Alice M. Horowitz - Myron Allukian, Jr., DDS, MPH (Blackwell Synergy, 2001)
Actually, I’m not sure how much more I can or should say about Alice. I was given no time limit or sense of direction. I’m musically and poetically challenged, and Alice provided no help, because she was always too busy. Also, as Alice is so serious and committed about her work, I wasn‘t sure if I should give a professional or humorous presentation, so I decided to try to do both. I know other speakers here tonight will detail Alice’s many outstanding achievements and contributions. I will speak from my perspective and experiences with Alice